2016
DOI: 10.1177/0956797616672464
|View full text |Cite
|
Sign up to set email alerts
|

When Far Becomes Near

Abstract: On many occasions, people spontaneously or deliberately take the perspective of a person facing them rather than their own perspective. How is this done? Using a spatial perspective task in which participants were asked to identify objects at specific locations, we found that self-perspective judgments were faster for objects presented to the right, rather than the left, and for objects presented closer to the participants' own bodies. Strikingly, taking the opposing perspective of another person led to a reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In addition, humans often mentally take contra-aligned perspectives in the horizontal, but not in the vertical plane. For instance, humans often take the spatial perspective of another person in interpersonal interactions (Cavallo, Ansuini, Capozzi, Tversky, & Becchio, 2017 ; Mainwaring, Tversky, Ohgishi, & Schiano, 2003 ; Schober, 1993 ; Tversky, Lee, & Mainwaring, 1999 ), which most likely take place in the horizontal plane and often with persons facing them (contra-aligned to themselves). Conceivably, such a greater extent of experience in spatial perspective taking might improve the efficiency in transforming an encoded perspective to infer the spatial relations from nonexperienced contra-aligned perspectives during retrieval.…”
mentioning
confidence: 99%
“…In addition, humans often mentally take contra-aligned perspectives in the horizontal, but not in the vertical plane. For instance, humans often take the spatial perspective of another person in interpersonal interactions (Cavallo, Ansuini, Capozzi, Tversky, & Becchio, 2017 ; Mainwaring, Tversky, Ohgishi, & Schiano, 2003 ; Schober, 1993 ; Tversky, Lee, & Mainwaring, 1999 ), which most likely take place in the horizontal plane and often with persons facing them (contra-aligned to themselves). Conceivably, such a greater extent of experience in spatial perspective taking might improve the efficiency in transforming an encoded perspective to infer the spatial relations from nonexperienced contra-aligned perspectives during retrieval.…”
mentioning
confidence: 99%
“…The novelty of the current study is that we confirmed that even in the smart home interface, a virtual environment, we still have the propensity to adopt the perspective of others. Considerable research has shown that we adopt others' perspectives as a result of the mere presence of others in a shared physical realm (Tversky and Hard, 2009;Kockler et al, 2010;Freundlieb et al, 2016;Furlanetto et al, 2016;Cavallo et al, 2017;Quesque et al, 2018). This propensity may be extended to the realm of mental activity, such as thinking and reading (Freundlieb et al, 2018), and even agentic features of inanimate objects such as an arrow (Zwickel, 2009;Heyes, 2014;Santiesteban et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to Tversky and Hard (2009), it is natural to take an egocentric reference frame, which refers to viewing the world through the perspective of the self. However, numerous recent studies have revealed that we adopt the visuospatial perspective of others when sharing physical space with others (Tversky and Hard, 2009;Kockler et al, 2010;Freundlieb et al, 2016;Furlanetto et al, 2016;Cavallo et al, 2017;Quesque et al, 2018). For example, we may explain the location of an object based on the perspective of another person sitting across from you by referring it to it as "the apple on your left" instead of "the apple on my right" (Cavallo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations